Lipid Delivery Systems for Nucleic-Acid-Based-Drugs: From Production to Clinical Applications - Anna Angela Barba; Sabrina Bochicchio; Annalisa Dalmoro; Gaetano Lamberti (MDPI AG, 2019)
In the last years the rapid development of Nucleic Acid Based Drugs (NABDs) to be used in gene therapy has had a great impact in the medical field, holding enormous promise, becoming “the latest generation medicine” with the first ever siRNA-lipid based formulation approved by the United States Food and Drug Administration (FDA) for human use, and currently on the market under the trade name Onpattro™. The growth of such powerful biologic therapeutics has gone hand in hand with the progress in delivery systems technology, which is absolutely required to improve their safety and effectiveness. Lipid carrier systems, particularly liposomes, have been proven to be the most suitable vehicles meeting NABDs requirements in the medical healthcare framework, limiting their toxicity, and ensuring their delivery and expression into the target tissues. In this review, after a description of the several kinds of liposomes structures and formulations used for in vitro or in vivo NABDs delivery, the broad range of siRNA-liposomes production techniques are discussed in the light of the latest technological progresses. Then, the current status of siRNA-lipid delivery systems in clinical trials is addressed, offering an updated overview on the clinical goals and the next challenges of this new class of therapeutics which will soon replace traditional drugs.